Lifestyle Interventions in the Treatment of Obsessive-Compulsive and Related Disorders: A Systematic Review. Issue 8 (October 2021) - Brierley, Mary-Ellen E.; Thompson, Emma M.; Albertella, Lucy; Fontenelle, Leonardo F.
ABSTRACT: Objective: Lifestyle medicine is increasingly important in psychiatry for its efficacy as a transdiagnostic treatment, its preventative potential, and its increased tolerability compared with first-line strategies. Although the impact of lifestyle medicine is strong across many psychiatric illnesses, our understanding of the effectiveness of lifestyle interventions in treating obsessive-compulsive and related disorders (OCRDs) is minimal. We aimed to conduct a systematic review examining the effect of lifestyle interventions (targeting diet, exercise, sleep, stress management, and tobacco/alcohol use) on OCRD symptoms. Methods: We systematically searched four electronic databases for published randomized controlled trials reporting on lifestyle interventions for OCRDs. We qualitatively synthesized results of eligible studies and calculated mean changes in symptom severity from baseline to end point and standardized between-group effect sizes. Results: We identified 33 eligible studies. Poor efficacy was noted across a number of rigorous dietary supplement interventions with some promising data in four (of six) studies regarding N -acetylcysteine for trichotillomania, skin picking, and obsessive-compulsive disorder. Stress management interventions, generally characterized by high risk of bias, reported mild effectiveness with greater effects noted for mind-body exercises (yoga) for obsessive-compulsive disorder. Greater improvements may be achieved when lifestyle intervention is adjunct to first-line treatments and delivered by facilitators. Conclusions: Diet (particularly N -acetylcysteine) and stress management interventions seem promising avenues for OCRDs treatment. We present an action plan to move the lifestyle interventions for OCRDs field forward. Further high-quality lifestyle interventions are required to improve the certainty of findings and to inform clinical treatment guidelines. Review Registration Number: CRD42020151407. Abstract : Supplemental digital content is available in the text.